The Role of Food Delivery Apps in Consumer Loyalty: A Study of GrabFood Users in Java - Qur'ani, Jasmine; Yuvista, Riska (Communicare : Journal of Communication Studies, 2025)
This research investigates the key factors influencing customer loyalty to the GrabFood app, with particular attention to price fairness, food quality, service quality, effort expectancy, and overall user satisfaction. The research employed a quantitative approach, using data collected from 250 GrabFood users residing on Java Island. selected through purposive sampling. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The findings indicate that food quality, service quality, and satisfaction have significant direct effects on loyalty. Satisfaction also acts as a strong mediating variable, especially for the effects of price fairness and effort expectancy on loyalty. Interestingly, price fairness and food/service quality showed negative indirect effects through satisfaction, suggesting a gap between user expectations and actual experience. Meanwhile, effort expectancy did not significantly influence loyalty directly, but positively affected satisfaction. This study highlights the critical role of user satisfaction in strengthening consumer loyalty. and recommends aligning service delivery with customer expectations.